2017
DOI: 10.1007/5584_2016_208
|View full text |Cite
|
Sign up to set email alerts
|

Small Airway Obstruction in Chronic Obstructive Pulmonary Disease: Potential Parameters for Early Detection

Abstract: The impulse oscillometry (IOS) is recognized as a complementary method to spirometry in the diagnostics of obstructive pulmonary disorders. The IOS enables to measure total respiratory resistance (R5) and proximal respiratory resistance (R20), with the R5-R20 difference reflecting small airway resistance. This study seeks to evaluate the usefulness of R5-R20, maximal mid-expiratory flow (MMEF) and forced expiratory volume in 3 s/forced vital capacity ratio (FEV/FVC), in the assessment of small airway obstructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…However, changes in FEF 25–75% are nonspecific and show an unacceptably large number of false-negative and false-positive results. Moreover, the reduction in FEF 25–75% values is a result of changes in the resistance and susceptibility of the surrounding lung parenchyma, rather than obstruction of a specific airway segment [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, changes in FEF 25–75% are nonspecific and show an unacceptably large number of false-negative and false-positive results. Moreover, the reduction in FEF 25–75% values is a result of changes in the resistance and susceptibility of the surrounding lung parenchyma, rather than obstruction of a specific airway segment [22].…”
Section: Discussionmentioning
confidence: 99%
“…When exposed to occupational dust, small airways are usually the primary damaged tissue in the lung because of the narrow diameters and the slow flow rate of air; therefore, particles were easily deposited in small airways (Bonini & Usmani, 2015; Piorunek et al, 2017). Previous studies reported that patients with coal worker's pneumoconiosis or asbestosis may have small airways damage during the early stages, and the prevalence rate of small airways dysfunction was positively related to the stages of pneumoconiosis and asbestosis (Corsico et al, 2003; Petsonk, Stansbury, Beeckman‐Wagner, Long, & Wang, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…When exposed to occupational dust, small airways are usually the primary damaged tissue in the lung because of the narrow diameters and the slow flow rate of air; therefore, particles were easily deposited in small airways (Bonini & Usmani, 2015;Piorunek et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed that pathological changes in the small airways do not necessarily entail spirometric abnormalities consistent with COPD diagnosis, so these pathological changes are also known as the "silent zone" of the lungs (29,30). Although mid-expiratory flow rates have been used to detect small airway dysfunction, they were not used for follow up because of a high degree of variability, which is why little has been known about the role of small airway dysfunction in the development of COPD until quite recently (31,32). The ability to distinguish between the small airway damage and emphysema has been improved by the recent development of parametric response mapping, which allows information from all lung voxels in an inspiratory multiple detector CT scan to be assigned to voxels present on an expiratory scan, making it possible to identify parts of the lungs with functional small airway disease (33).…”
Section: Discussionmentioning
confidence: 99%